Evaluation on the effects of relaxing music on the recovery from aerobic exercise-induced fatigue - Jing, L.; Xudong, W. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. There are few researches on the effects of music therapy on the recovery from exercise-induced fatigue worldwide. The aim of this study was to evaluate the effects of relaxing music on aerobic exercise-induced fatigue. The authors' hypothesis is that relaxing music can effectively eliminate aerobic exercise-induced fatigue. Methods. Thirty healthy male college students were randomly assigned to either no-music group or music group. All the subjects maintained the pedal cadence of 50 rev€min-1 on a cycle ergometer until fatigue. Then subjects in music group listened to relaxing music for 15 minutes, while subjects in no-music group had a 15-minute rest without music. Heart rates, jump height, blood glucose, blood lactic acid, urinary protein, simple reaction time and ratings of perceived exertion (RPE) were determined before and after the 15-minute treatment for each group. Results. The results showed that heart rates, urinary protein and RPE decreased significantly after the application of relaxing music (P<0.01), and these decreases were greater than those without music. Conclusion. The results suggest that relaxing music has better effects on the rehabilitation of cardiovascular, central, musculoskeletal and psychological fatigue and the promotion of the regulatory capability of the kidneys.